The Effects of Glycerol Supplement on Plasma Aldosterone Levels in Sedentaries - Patlar, Süleyman; Keskin, Ercan; Çakmakçı, Oktay (Fırat University, 2007)
Objectives: The aim of this study is to search the effects of the glycerol supplement on the levels of plasma aldosteron of sedentaries. Material and Method: In this study, 20 students with an average age of 22.82 ± 1.49 year and an average weight of 73.96 ± 9.16 kg, who attend currently at the other faculties of Selçuk University, were used as subjects. Subjects were divided into two groups which were sedentaries (S) and sedentaries supplemented with glycerol (GS). The test of shuttle and run of 20 meters was applied to subjects in the groups S and GS at the end of 20th days. Subjects of the group GS were supplemented orally 1,5 lt water with the dose of 1.2 g/kg of glycerol at ten o'clock every morning during the period of twenty days. At the same time, samples of blood were taken from all the subjects before tests and supplemented with glycerol. Besides, samples of blood were taken from subjects only in the group GS after the supplemented with glycerol. At the end of 20th days, the specified exercise tests were applied to two groups after the second blood test. Just after the exercise tests, samples of blood were taken from the subjects the third time. Then, the samples of blood were taken from them two hours later after the exercises the fourth time and also twenty four hours later after the same exercises the fifth time again. Results: The level of plasma aldosteron of blood samples of all groups was almost similar in 5 measured. The level of plasma aldosteron of blood samples of all groups just after exercise was higher significantly than that before exercise (p

Giriş: Bu çalışmanın amacı, sedanterlerde gliserol uygulamasının plazma aldosteron düzeylerini nasıl etkilediğini araştırmaktır. Gereç ve Yöntem: Çalışma yaş ortalamaları 22.82±1.49 yıl ve vücut ağırlığı ortalamaları 73.96±9.16 kg olan ve Selçuk Üniversitesi'nin değişik fakültelerinde okuyan 20 sağlıklı erkek üzerinde gerçekleştirildi. Denekler iki gruba (Sedanter grup (S), Gliserol takviyeli sedanter grup (GS) ayrıldı. Her iki gruptaki deneklere 20. günün sonunda 20 m mekik koşu testi uygulandı. GS grubuna dahil olan deneklere 20 gün boyunca sabah saat 10.00'da oral olarak 1.2 g/kg dozunda gliserol 1.5 lt su ile karıştırılarak takviye yapıldı. Bütün deneklerden egzersiz periyoduna ve gliserol takviyesine başlamadan önce kan örnekleri alındı. Ayrıca, 20 günlük gliserol takviyesinden sonra tüm deneklerden ikinci kan örnekleri alındı. 20. günün sonunda her iki gruba da belirtilen egzersiz testi uygulandı. Egzersiz testinin bitiminden hemen sonra üçüncü kan örnekleri alındı. Egzersizden 2 saat sonra dördüncü ve 24 saat sonra besinci kan örnekleri alındı. Alınan kan örneklerinde belirlenen plazma aldosteron düzeyleri ölçüldü.. Bulgular: Her iki grubun aldosteron düzeyleri yapılan 5 ölçümde de birbirinden farklı değildi. Egzersizden hemen sonra hem GS, hem de S grubunun plazma aldosteron düzeyleri egzersiz öncesi değerlerden önemli şekilde yüksekti (p
Sedanterlerde Gliserol Takviyesinin Plazma Aldosteron Düzeyleri Üzerine Etkisi